A simple and effective method for bladder blood clot evacuation using hydrogen peroxide. Issue 5 (May 2020) - Xu, Ming; Jin, Lu; Shan, Yuxi; Zhu, Jin; Xue, Boxin
Objective: Urinary retention caused by bladder clots can be frustrating because such blood clots are difficult to remove. We established a novel technique in which hydrogen peroxide is applied to evacuate bladder clots. Methods: In this single-center retrospective study, we evaluated 31 patients with retention of blood clots in the bladder who underwent emergency evacuation using hydrogen peroxide. Results: The patients comprised 17 men and 14 women with mean age of 61.2 years (range, 42–82 years). Hydrogen peroxide solution and a 20-Fr three-cavity Foley catheter with large-diameter side holes were used for manual bladder irrigation in all patients. The bladder blood clots were successfully removed in 27 patients. The remaining four patients could not tolerate the symptoms of urinary retention and had to resort to surgery. Conclusion: Hydrogen peroxide solution for manual bladder irrigation can improve the efficiency of bladder blood clot evacuation. This is a simple and effective option for managing bladder clot retention.